The Effect of Sevoflurane and Propofol on the Status of Renal Complications in Traumatic Injury Patients Following Laminectomy Surgery - hassanreza mohammadi; Ali Erfani; Aminollah Vasigh; Hosein Karimiyarandi; Sohrab Sadeghi (Bulletin of Emergency and Trauma)
Objectives: Laminectomy is one of the most prevalent back surgeries. Considering the importance of controlling and minimizing surgical complications, this study was conducted to determine the effect of Sevoflurane and Propofol on the state of renal complications in patients undergoing laminectomy surgery.Methods: This clinical trial was conducted in Ilam (Iran). The study used a double-blind random sampling procedure, and the patients were divided into three groups receiving Sevoflurane (n=25), Propofol (n=25), and the combination of Sevoflurane and Propofol (n=25). The research tool included a checklist of demographic characteristics as well as a clinical examination. Kidney complications were diagnosed based on history, clinical examinations, and laboratory test results. The obtained data were analyzed using SPSS software.Results: In this study, the patient’s mean age in the Propofol group was 52.4±5.6, the Sevoflurane group was 50.8±2.5, and Sevoflurane plus Propofol group was 53.5±3.4. The Sevoflurane plus Propofol group had the highest rate of urinary retention (n=7, 28%). In addition, there was no difference between laboratory results of creatinine and urinary retention in the studied groups (P>0.05). Besides, the comparison of the mean of renal laboratory indicators in the research patients indicated that the level of serum creatinine, and cystatin C of the patients had no significant change.Conclusion: There was no significant difference between the complications in the three groups. Therefore, all three drugs can be administered to patients.